May–Thurner syndrome and other obstructive iliac vein lesions: Meaning, myth, and mystery. (February 2015) - Birn, Jeffrey; Vedantham, Suresh
Acute and chronic venous disorders of the lower extremities affect millions of people and cause substantial disability. Long ago, surgeons and pathologists identified the presence of 'spur-like' abnormalities of the left common iliac vein; these abnormalities were hypothesized to result from compression and/or irritation from the adjacent crossing right common iliac artery. In the 1990s, physicians, starting to perform catheter-directed thrombolysis to treat extensive deep vein thrombosis (DVT), observed that about 50% of patients had an iliac vein stenosis. Vascular physicians have become aware of the occasional patient with otherwise-unexplained extremity swelling and/or pain but without a DVT history who is subsequently found to have an iliac vein abnormality. These 'lesions' have been hypothesized to elevate ambulatory venous pressures and thereby produce lower-extremity symptoms, increase the risk of initial and recurrent DVT episodes, and increase the risk of treatment failure with medical and endovascular therapies for thrombotic and non-thrombotic venous conditions. As a result, many practitioners now actively seek iliac venous obstructive 'lesions' when evaluating patients with known or suspected venous disease. However, for many patients, it continues to be unclear what degree of obstruction to venous blood flow is being caused by such lesions, how clinically significant they are, how much emphasis should be placed on identifying them, and when they should be treated. This article seeks to improve the knowledge base of vascular practitioners who make clinical decisions about the diagnosis and treatment of obstructive iliac vein lesions.